2022
DOI: 10.1111/ele.14086
|View full text |Cite
|
Sign up to set email alerts
|

Resource limitation determines realized thermal performance of consumers in trophodynamic models

Abstract: Recent work has demonstrated that changes in resource availability can alter a consumer's thermal performance curve (TPC). When resources decline, the optimal temperature and breadth of thermal performance also decline, leading to a greater risk of warming than predicted by static TPCs. We investigate the effect of temperature on coupled consumer‐resource dynamics, focusing on the potential for changes in the consumer TPC to alter extinction risk. Coupling consumer and resource dynamics generally reduces the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 83 publications
0
17
0
Order By: Relevance
“…A thermal mismatch refers to trophic levels having different temperature optima and/or thermal niches (Dell et al, 2014). Analyses have shown that such a mismatch will affect community dynamics and realised thermal niches (Amarasekare, 2015;Vinton & Vasseur, 2022). Our results show that, when the size of the feasibility domain is the response variable, such a mismatch will not consistently hamper or promote coexistence.…”
Section: New Insightsmentioning
confidence: 77%
See 1 more Smart Citation
“…A thermal mismatch refers to trophic levels having different temperature optima and/or thermal niches (Dell et al, 2014). Analyses have shown that such a mismatch will affect community dynamics and realised thermal niches (Amarasekare, 2015;Vinton & Vasseur, 2022). Our results show that, when the size of the feasibility domain is the response variable, such a mismatch will not consistently hamper or promote coexistence.…”
Section: New Insightsmentioning
confidence: 77%
“…The identified communities are listed in Table S1; statistical results are in Table S2. Many analyses of environmental change effects on consumer-resource communities consider cases where a single resource feeds a single consumer, as this is a fundamental building block of more complex models (Amarasekare, 2015;Synodinos et al, 2021;Turschwell et al, 2022;Uszko et al, 2017;Vinton & Vasseur, 2022). In most of these cases, positive consumer density guarantees the feasibility of the species pair, as the consumer cannot persist without the resource.…”
Section: New Insightsmentioning
confidence: 99%
“…Despite the theoretical basis describing how a population's equilibrium (i.e. carrying capacity) ought to respond to multiple stressors (Vinton & Vasseur, 2022), population dynamics involve nonlinearities that make equilibrium behaviour just the starting point for forecasting responses to variable environments (Hastings et al, 2018). Under the rapid pace of global change, how populations will track changes in the mean and variance of the environment remains to be seen, as vital rates and underlying equilibria may be changing simultaneously.…”
Section: Carling Biegmentioning
confidence: 99%
“…Previous work has established that the optimum for thermal performance (here measured by the per-capita growth rate dB/Bdt) decreases under nutrient limitation due to the non-linearity of the two terms in Equation 9 (Thomas et al, 2017;Vinton & Vasseur, 2022). Under limiting nutrients, N cannot be factored out in the derivation of Equation ( 9) (though it retains the same general shape) and nutrient limitation therefore scales this curve.…”
Section: Integrating Thermal Responses Into a Thermal Performance Curvementioning
confidence: 99%
See 1 more Smart Citation